Various ORSV infection symptoms on ceratorhiza induction in orchid plants - Mitha Valentina Treesya Panjaitan; Mahfut Mahfut; Tundjung Tripeni Handayani; Sri Wahyuningsih (Journal of Sustainability Science and Technology, 2021)
Several types of orchids that are in great demand and cultivated by various groups are Phalaenopsis sp. and Dendrobium sp. Mycorrhizae are needed by orchid plants to complete their life cycle. This is because mycorrhizae are capable of symbiosis with the root system of the host plant so that the plant's capacity to absorb elements will increase. This study aims to determine the extent to which Ceratorhiza induction on Phalaenopsis amabilis and Dendrobium discolour orchids can suppress the symptoms of Odontoglossum ringspot virus (ORSV) infection. The method used in this study was a factorial completely randomized design (CRD) with 2 factors and 4 replications. The first factor is the type of orchid used, namely Phalaenopsis amabilis (A1) and Dendrobium discolour (A2), while the second factor is the type of administration of mycorrhizae, viruses, and mycorrhizal viruses. Observation of disease symptoms is done by looking at the symptoms that appear on leaves that have been infected with ORSV. The results showed that the symptoms that appeared in Phalaenopsis amabilis were in the form of mosaic, necrosis, leaf malformation, while in Dendrobium discolour were mosaic and necrotic. Ceratorhiza was not able to suppress the symptoms of disease infection because based on the results obtained; the treatment on orchids inoculated with mycorrhizae and viruses showed more severe symptoms compared to the treatment only inoculated with viruses increased response and Dendrobium discolours showed a decreased response in leaf length, width, and number. Meanwhile, in the root organ, Dendrobium discolour showed an increased response and Phalaenopsis amabilis showed a decreased response in root length and number of roots.